The impact of urban transport systems on the physical-spatial transformations of the city: The example of the Constantine tramway - Diabi, Amina; Lazri, Youcef (Journal of Architecture and environment of child, 2022)
The transformations that the city has considered through time have affected so considerably its urban space, bringing it a certain remodeling and a new new physionomy. This constant change is conditioned by multiple factors, of which transport has always been a part. Today, the tramway as a modern mode of transport, is considered a powerful tool that accompanies the urban space in its mutation. The purpose of this article is to determine the physical-spatial transformations in Constantine, due to the installation of the tramway line.It is from the observation of the different transformations affecting the spaces surrounding the tramway line (road space, public space, built space), that this analysis is realized. The results show that the developments that accompanied this insertion were subject to many transformations on a physical-spatial scale: a reorganized street network, a shared and renewed roadway, new facilities installed (street furniture, public lighting, traffic signage, etc), requalified public spaces, and rehabilitated facades. But, unfortunately, they didn’t reach the point of generating great changes in the urban space adjacent to the line.